Comparison of cryobiopsy and forceps biopsy for the diagnosis of mediastinal lesions: a randomised clinical trial - Cheng, T.L.; Huang, Z.-S.; Zhang, J.; Wang, J.; Zhao, J.; Kontogianni, Konstantina; Fu, W.-L.; Wu, N.; Kuebler, W.M.; Herth, Felix; Fan, Ye (Pulmonology, 2024)
Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is the standard approach for lung cancer staging. However, its diagnostic utility for other mediastinal diseases might be hampered by the limited tissue retrieved. Recent evidence suggests the novel sampling strategies of forceps biopsy and cryobiopsy as auxiliary techniques to EBUS-TBNA, considering their capacity for larger diagnostic samples. This study determined the added value of forceps biopsy and cryobiopsy for the diagnosis of mediastinal diseases. Consecutive patients with mediastinal lesions of 1 cm or more in the short axis were enrolled. Following completion of needle aspiration, three forceps biopsies and one cryobiopsy were performed in a randomised pattern. Primary endpoints included diagnostic yield defined as the percentage of patients for whom mediastinal biopsy led to a definite diagnosis, and procedure-related complications. In total, 155 patients were recruited and randomly assigned. Supplementing EBUS-TBNA with either forceps biopsy or cryobiopsy increased diagnostic yield, with no significant difference between EBUS-TBNA plus forceps biopsy and EBUS-TBNA plus cryobiopsy (85.7 % versus 91.6 %, P = 0.106). Yet, samples obtained by additional cryobiopsies were more qualified for lung cancer molecular testing than those from forceps biopsies (100.0 % versus 89.5 %, P = 0.036). When compared directly, the overall diagnostic yield of cryobiopsy was superior to forceps biopsy (85.7 % versus 70.8 %, P = 0.001). Cryobiopsies produced greater samples in shorter procedural time than forceps biopsies. Two (1.3 %) cases of postprocedural pneumothorax were detected. Transbronchial mediastinal cryobiopsy might be a promising complementary tool to supplement traditional needle biopsy for increased diagnostic yield and tissue harvesting. ChiCTR2000030373
Gesehen am 02.09.2025